Crystallographic, Optical, and Electronic Properties of the Cs2AgBi1–xInxBr6 Double Perovskite: Understanding the Fundamental Photovoltaic Efficiency Challenges - Schade, Laura; Mahesh, Suhas; Volonakis, George; Zacharias, Marios; Wenger, Bernard; Schmidt, Felix; Kesava, Sameer Vajjala; Prabhakaran, Dharmalingam; Abdi-Jalebi, Mojtaba; Lenz, Markus; Giustino, Feliciano; Longo, Giulia; et al. (My University, 2021)
We present a crystallographic and optoelectronic study of the double perovskite Cs2AgBi1-xInxBr6. From structural characterization we determine that the indium cation shrinks the lattice and shifts the cubic-to-tetragonal phase transition point to lower temperatures. The absorption onset is shifted to shorter wavelengths upon increasing the indium content, leading to wider band gaps, which we rationalize through first-principles band structure calculations. Despite the unfavorable band gap shift, we observe an enhancement in the steady-state photoluminescence intensity, and n-i-p photovoltaic devices present short-circuit current greater than that of neat Cs2AgBiBr6 devices. In order to evaluate the prospects of this material as a solar absorber, we combine accurate absorption measurements with thermodynamic modeling and identify the fundamental limitations of this system. Provided radiative efficiency can be increased and the choice of charge extraction layers are specifically improved, this material could prove to be a useful wide band gap solar absorber.
Keywords: Bismuth compounds; Bromine compounds; Calculations; Cesium compounds; Efficiency; Electronic properties; Energy gap; Indium; Perovskite; Perovskite solar cells; Phase transitions; Silver compounds